Confidence-driven control of an ultrasound probe: Target-specific acoustic window optimization - Chatelain, Pierre; Krupa, Alexandre; Navab, Nassir (Proceedings - IEEE International Conference on Robotics and Automation, 2016)
We propose a control framework to optimize the quality of robotic ultrasound imaging while tracking an anatomical target. We use a multitask approach to control the in-plane motion of a convex probe mounted on the end-effector of a robotic arm, based not only on the position of the target in the image, but also on features extracted from an ultrasound confidence map. The resulting control law therefore guarantees a good image quality, while keeping the target aligned with the central ultrasound scan-line. Potential applications of the proposed approach are, for example, teleoperated ultrasound examination, motion compensation for ultrasound-guided interventions, or automatic ultrasound acquisition. We demonstrate our approach with experiments on an ultrasound examination training phantom in motion.
CRIS-Team Scopus Importer:2023-03-08